The fuel cell electric vehicle market growth: Analyses of contracts and government incentives. (February 2023) - Toktaş-Palut, Peral
Highlights: The contracts are more effective than incentives for the FCEV market growth. The fuel price contract leads to the highest market demand and annual profits. The supplementary subsidy contract increases profits per investment. Capital cost-based incentives accelerate to reach a target market size. Consumer-oriented and operating cost-based incentives enhance the market demand. Abstract: Climate change has emerged as one of the most challenging problems facing the world. Due to the greenhouse gas emissions of gasoline and diesel-powered vehicles, automakers have introduced more eco-friendly products, such as fuel cell electric vehicles (FCEVs). However, despite government policies and collaborations, the market share of FCEVs is far below the target level. Hence, this paper focuses on the FCEV market growth and analyzes the effects of contracts and government incentives. The fuel price (FP) and supplementary subsidy (SS) contracts are developed for collaborating a hydrogen supplier and automaker framework. Furthermore, four different government incentives are examined. The results imply that incentives supporting the capital costs are more effective in the startup phase to increase the number of companies entering the market and accelerate to reach a target market size. On the other hand, consumer-oriented and operating cost-based incentives are more capable of market demand enhancement and growth. Only the tax credit of 8, 000 USD generates higher market demand and annual profits than the contracts in some cases, and both contracts dominate all the other incentives. Hence, depending solely on government incentives will not be enough for market growth, and it will take ages to reach a target market size without contracts. The stakeholders with sufficient initial capital can prefer the FP contract to achieve the highest market demand and annual profits. If the stakeholders have less capital, they can apply the SS contract to earn higher profits per investment. Both contracts are strict Pareto improving and fair.